The Bottleneck Metaphor of Leadership Culture: How Shared Understandings About Leadership Develop in Groups and Impede Diversity and Effectiveness of Leaders - Özcan, Muaz (Frontiers in Psychology, 2021)
There are two big problems related to leadership today: unequal representation and high failure rates among leaders. This conceptual paper argues that commonly shared values, assumptions, and beliefs about leadership, i.e., universal leadership culture, is the common cause of both problems. After the concepts and levels related to leadership culture were explained, we introduced a multi-level, multi-actor process model named the bottleneck metaphor of leadership culture. This metaphor explains how leadership cultures are co-constructed by multiple actors and reproduce themselves in groups over time based on emergent leaders' characteristics. Next, a diagnostic tool called "the leadership mirror" is proposed for organizations that want to assess their leadership cultures' current state as a starting point for further interventions. Specific suggestions are made for various actors ranging from individuals to organizations for their possible roles in preventing undesired leadership cultures.